2017
DOI: 10.1587/nolta.8.204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a root-raised-cosine filter on a BPSK stochastic resonance receiver

Abstract: Signal filtering is necessary for wireless communication. However it causes the signal amplitude to fluctuate and affects the performance of stochastic resonance (SR) receivers. In this study, we evaluate the bit error rate (BER) performance of filtered binary phase-shift keying (BPSK) on an SR receiver. The results show that filtering improves the BER performance of the SR receiver because the amplitude fluctuation contributes to improving the SR effect. We also evaluate the effect of the roll-off factor, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, a three-level device was employed as the nonlinear system [21,22,24]. The inputoutput characteristics of this system are shown in Fig.…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a three-level device was employed as the nonlinear system [21,22,24]. The inputoutput characteristics of this system are shown in Fig.…”
Section: System Modelmentioning
confidence: 99%
“…Thus, a weak attenuated signal may be below the limit, resulting in detection failure. To solve this problem, the effectiveness of receivers exploiting SR has been investigated [18][19][20][21][22][23][24]. With the noise intensity set to the optimal value, it has been revealed that the digital phase of the transmitted signal can be obtained by the receiver [20].…”
Section: Introductionmentioning
confidence: 99%